Vietnam : Renewable Energy Action Plan - Bogach, V. Susan (World Bank, Washington, DC, 2014)
The Renewable Energy Action Plan (REAP) was prepared in a participatory workshop with stakeholders, to discuss renewable energy potential, problems, and solutions, and synthesize study results into a draft action report. The objective of the REAP is to provide cost-effective, and reliable electricity to rural populations, by supplying isolated households, and communities with renewable sources of energy, and augmenting grid supply in remote areas. The capacity-building phase will build on the renewable energy policy, and institutional development, support individual household and institutional renewable energy systems, through the provision of mini-grids based on hydro-hybrid plants. To this end technical assistance, and investment support will be provided to encourage small power producers of renewable electricity for grid supply, from small hydro, bagasse, or rice husk cogeneration, while other technologies will also be supported, such as wind power. Lessons learned from the REAP experience address the need to ensure a policy, and legal framework to guide private sector involvement, by first building capacity, and a strong institutional support, to understand market characteristics, and support development of commercial renewable energy businesses, to include financial intermediation, and micro-finance.